Preservation of protein fractions and hormones of placental blood serum after freeze-drying - Shevchenko, Mariia; Skoryk, Anastasiia; Salnykov, Dmytro; Gorina, Olga; Ivanov, Yevhen; Lazurenko, Victoria; Prokopiuk, Olga (Problems of Cryobiology and Cryomedicine, 2026)
The preservation of placental blood serum (PBS) following freeze-drying was studied, factoring in the course of pregnancy in parturient women. Placental blood was obtained from women with a physiological pregnancy, premature births, and concomitant autoimmune thyroiditis or hypertension. Serum was obtained by separating the supernatant after centrifugation of placental blood. After freeze-drying, the concentration of total protein and the ratio of protein fractions in the PBS were determined by the biuret method, and the levels of prolactin, human chorionic gonadotropin (hCG), alpha-fetoprotein (AFP), cortisol and somatotropin (STH) were measured by the enzyme-linked immunosorbent assay. It was found that the composition of the PBS depended on the course of pregnancy. Extragenital pathology is accompanied by a redistribution of protein fractions and changes in prolactin, AFP, STH and hCG levels. After freeze-drying the PBS from healthy parturients, the studied parameters did not differ from those in native serum, whereas in cases of complicated pregnancy, changes in the ratio of protein fractions were observed. Probl Cryobiol Cryomed. 2026;36(1):58—65